Hubungan Ibu Preeklamsia dengan Kejadian Berat Badan Lahir Rendah (BBLR) - Rozani, Leni; Ferasinta, Ferasinta; Panzilion, Panzilion; Novitasari, Selvia (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Preeclampsia is hypertension accompanied by proteinuria that occurs during pregnancy, childbirth or the puerperium. Low birth weight (LBW) is a baby weighing 2500 grams or less at birth regardless of gestational age. These newborns are considered to have intrauterine growth rates less than expected or a shortened gestational age. The purpose of this study was to determine the frequency distribution of preeclampsia and low birth weight, and the relationship between preeclampsia and low birth weight. The research design used in this study was a case control design, namely a research design consisting of a control group and a case group, the respondents in this study totaled 94 people, 47 people in the control group and 47 people in the case group. From the results of the study, the univariate analysis obtained the results of each variable, 48 mothers who experienced preeclampsia with a percentage of 51.1% and 46 mothers who did not experience preeclampsia with a percentage of 48.9%, in the LBW frequency distribution table there were 47 babies who experienced LBW babies (case group), and babies who did not have LBW babies totaled 47 babies (control group). In the bivariate analysis, the results of the chi square test showed that the p value = 0.000 < , so there is a strong relationship, Ho is rejected and Ha is accepted. This means that there is a relationship between the incidence of preeclampsia and low birth weight (LBW), so that with research explaining that preeclampsia mothers can give birth to babies with LBW babies, it is hoped that mothers can maintain their health during pregnancy until delivery, examine their pregnancies from the start until delivery, recognize symptoms early -symptoms of diseases that arise during pregnancy so that treatment can be carried out optimally. Keywords: Preeclampsia, and LBW  ABSTRAK Preeklamsia adalah hipertensi disertai proteinuria yang timbul selama kehamilan, persalinan atau masa nifas. Berat badan lahir rendah (BBLR) adalah berat bayi 2500 gram atau kurang pada saat lahir tanpa memandang usia kehamilan. Bayi baru lahir ini dianggap mengalami kecepatan pertumbuhan intrauterine kurang dari yang diharapkan atau pemendekan masa gestasi. Tujuan dari penelitian ini untuk mengetahui distribusi frekuensi kejadian preeklamsia dan BBLR, dan hubungan antara kejadian preeklamsia dengan BBLR. Desain penelitian yang digunakan dalam penelitian ini adalah desain case control yaitu rancangan penelitian yang terdiri dari kelompok kontrol dan kelompok kasus, responden dalam penelitian ini berjumlah 94 orang, 47 orang kelompok kontrol dan 47 orang kelompok kasus. Dari hasil penelitian, pada analisis univariat didapatkan hasil dari masing-masing variabel, 48 ibu yang mengalami preeklamsia dengan persentase 51,1%  dan 46 ibu yang tidak mengalami preeklamsia dengan persentase 48,9%, pada tabel distribusi frekuensi BBLR terdapat 47 bayi yang mengalami BBLR (kelompok kasus), dan bayi yang tidak mengalami BBLR berjumlah 47 bayi (kelompok kontrol). Pada analisis bivariat  didapatkan hasil uji chi square, nilai p value = 0.000 < , jadi ada hubungan yang kuat, Ho ditolak dan Ha diterima. Artinya ada hubungan kejadian preeklamsia dengan berat badan lahir rendah (BBLR), sehingga dengan adanya penelitian yang menjelaskan bahwa ibu preeklamsia dapat melahirkan bayi yang BBLR diharapkan para ibu dapat menjaga kesehatan selama hamil sampai persalinan, memeriksa kehamilan sejak awal sampai persalinan, mengenali sejak dini gejala-gejala penyakit yang timbul saat hamil agar penanganan dapat dilakukan dengan maksimal.         Kata Kunci: Preeklamsia, dan BBLR